2023
DOI: 10.1186/s12905-023-02613-8
|View full text |Cite
|
Sign up to set email alerts
|

Syrian refugee women’s access to family planning services and modern contraception during overlapping crises in Bekaa, Lebanon

Rima Mourtada,
Andrea J. Melnikas

Abstract: Background Political, financial, and pandemic crises in Lebanon have affected both provision of reproductive health services including family planning and modern contraception methods as well as women’s interest and ability to seek those services. This study aims to explore the impact of the compounding crises on the provision and use of family planning services including modern contraception methods for Syrian refugees in Lebanon focusing on the perspectives of Syrian refugee women. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…It is evident that women have no access to FP services because they are not only unfamiliar with the environment but also on mobility. This finding is supported by studies done in Turkiye and Lebanon [ 37 , 38 ] which revealed that refugee women during mobility have little or no access to FP services. Some of the reasons are language barrier, limited information about FP, no method of choice among others.…”
Section: Discussionsupporting
confidence: 69%
“…It is evident that women have no access to FP services because they are not only unfamiliar with the environment but also on mobility. This finding is supported by studies done in Turkiye and Lebanon [ 37 , 38 ] which revealed that refugee women during mobility have little or no access to FP services. Some of the reasons are language barrier, limited information about FP, no method of choice among others.…”
Section: Discussionsupporting
confidence: 69%
“…The study found that since 2019, disruption of reproductive health services that provide family planning and modern contraception, as well as the reduced supply of modern contraception methods were major outcomes of Lebanon's economic demise and its COVID-19 restrictions (Mourtada and Melnikas, 2023). According to the same study, women also reported "financial limitations in accessing and paying for services, " and "concerns about insecurity" as major contributors to the decrease in their access to quality gendersensitive care (Mourtada and Melnikas, 2023).…”
Section: The De-prioritization and Fragility Of Gender-sensitive Heal...mentioning
confidence: 98%
“…A 2023 study published in BMC Women's Health that explored the impact of Lebanon's compounding crises on the provision and use of family planning services including modern contraception methods for Syrian refugee women in the Beqaa found these types of gender-focused services were largely impacted by the local and national contexts (Mourtada and Melnikas, 2023). The study found that since 2019, disruption of reproductive health services that provide family planning and modern contraception, as well as the reduced supply of modern contraception methods were major outcomes of Lebanon's economic demise and its COVID-19 restrictions (Mourtada and Melnikas, 2023). According to the same study, women also reported "financial limitations in accessing and paying for services, " and "concerns about insecurity" as major contributors to the decrease in their access to quality gendersensitive care (Mourtada and Melnikas, 2023).…”
Section: The De-prioritization and Fragility Of Gender-sensitive Heal...mentioning
confidence: 99%